Breastfeeding: helping mothers at home, after discharge from hospital. A descriptive study - Rosa Aurea Quintella Fernandes; Ana Claudia de Lima Lara (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The problems mother face during breastfeeding may lend to early weaning. The period after discharging from hospital is critical, since woman not always find support and orientation to successfully overcome this phase. The purpose of this descriptive, exploratory study was to identify the difficulties mothers have to face during breastfeeding, after discharging from hospital and to guide them, by means of telephone calls. 64 women who gave birth at a private hospital were interviewed in September and October 2003. The results showed that mothers had a good level of education, 65% had finished the secondary school and 30% higher education. A the moment of the telephone call, which occurred in the 8th and 9th day after birth, 95% were exclusively breastfeeding and 92% did not mention any difficulties. However, 61% of theses women presented fissure between the 3rd and 4th day and 23%continnued having this problem. Breast engorgement mentioned by 19% of the breast-feeding women, occurred between the 4th and 5th day. It was concluded that the telephone approach helped some mothers to immediately overcome problems while others were referred to nursing consultation as the hospital. These difficulties could be overcome more efficiently if contacts occurred earlier.